Plasma-derived exosomal immunoglobulins IGHV4-4 and IGLV1-40 as new non-small cell lung cancer biomarkers - Yang, Peng; Zhang, Yang; Zhang, Ruping; Wang, Yun; Zhu, Shengjin; Peng, Xin; Zeng, Yimin; Yang, Bing; Pan, Meijun; Gong, Jie; Ba, Hongping (American journal of cancer research, 2023)
Exosomal proteins represent valuable research directions in the liquid biopsy of lung cancer (LC). Immunoglobulin subtypes, immunoglobulin molecules with different domains in variable regions, are products of B cell responses to different tumor antigens and are associated with tumor incidence and development. The plasma of patients with LC should theoretically contain a large number of B cell-derived exosomes that specifically recognize tumor antigens. This paper intended to assess the value of the proteomic screening of plasma exosomal immunoglobulin subtypes for diagnosing non-small cell LC (NSCLC). The plasma exosomes of NSCLC patients and healthy control participants (HCs) were isolated using ultracentrifugation. Label-free proteomics was employed to assess the differentially expressed proteins (DEPs), while the biological characteristics of the DEPs were analyzed using GO enrichment. The immunoglobulin content in the top two fold change (FC) values of the DEPs and the immunoglobulin with the lowest -value were verified using an enzyme-linked immunosorbent assay (ELISA). The differentially expressed immunoglobulin subtypes verified via ELISA were selected to statistically analyze the receiver operating characteristic curve (ROC), after which the diagnostic values of the NSCLC immunoglobulin subtypes were determined via the ROC area under the curve (AUC). The plasma exosomes of the NSCLC patients contained 38 DEPs, of which 23 were immunoglobulin subtypes, accounting for 60.53%. The DEPs were mainly related to the binding between immune complexes and antigens. The ELISA results showed significant differences between the immunoglobulin heavy variable 4-4 (IGHV4-4) and immunoglobulin lambda variable 1-40 (IGLV1-40) in the LC patients and HCs. Compared with the HCs, the AUCs of IGHV4-4, IGLV1-40, and a combination of the two in diagnosing NSCLC were 0.83, 0.88, and 0.93, respectively, while the AUCs for non-metastatic cancer were 0.80, 0.85, and 0.89. Moreover, their diagnostic values for metastatic cancer compared to non-metastatic cancer displayed AUCs of 0.71, 0.74, and 0.83, respectively. When IGHV4-4 and IGLV1-40 were combined with serum CEA to diagnose LC, the AUC value increased, exhibiting values of 0.95, 0.89, and 0.91 for the NSCLC, non-metastatic, and metastatic groups, respectively. Plasma-derived exosomal immunoglobulins containing IGHV4-4 and IGLV 1-40 domains can provide new biomarkers for diagnosing NSCLC and metastatic patients.